Clinical evaluation of bulk-fill composite resin and layered composite resin restoration in class I cavity of permanent molar teeth - Talukder, Mohammad Fida Hasan; Hossain, Mozammal; Moral, Mohammad Ali Asgor (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
The purpose of the present study was to compare the clinical performance of bulk-fill composite resin with that of layered composite resin restorations in occlusal class I cavity of permanent molar teeth. This study includes a total of 104 teeth having class I cavity of 3-4 mm depth in the occlusal surface. They were restored either with layered composite resin or bulk-fill composite resin of 52 teeth in each group. To observe the retention, marginal adaptation and color match, all restorations were assessed by using modified United States Public Health Services (USPHS) and Ryge’s criteria at baseline, 3, 6 and 12 months. The results of 12 months observation showed that retention of 38 layered composite and 48 bulk-fill composite resin restorations revealed alpha rating, which was statistically significant. The marginal adaptation of 37 layered composite resin and 47 bulk-fill composite resin restorations also demonstrated alpha rating and the differences between two groups were statistically significant. However, there were no significant differences between the layered composite resin and bulk-fill composite resin restorations in respect to color match. It can be concluded that bulk-fill composite resin showed better clinical outcome than that of layered composite resin in the restorations of occlusal class I cavity.